A study of binding serum albumin proteins with β-carboline alkaloids :Critical for pharmacological action of various drugs - Qadir, Anmbiya; Khuroo, Mohammad Akbar; Akbar, Iqrah; Jamal, Parveen (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
β-Carboline alkaloids present in Peganum harmala L. (harmal) have recently drawn attention due to their antitumor activities. Bovine Serum Albumin (BSA) is the major soluble protein constituent of the circulatory system, and has many physiological functions including the transportation of various compounds as ligands. In this study the binding of β-carboline alkaloids to Bovine Serum Albumin (BSA) has been investigated by using a constant protein concentration and varying drug concentrations. The binding modes of β-carboline alkaloids were analyzed by using FTIR and UV–Vis spectroscopic methods. Spectroscopic evidence showed that β-carboline alkaloids bind BSA via hydrophobic interaction and Vander Waals contacts along with Hbonding with the–NH groups.